Beethoven Prometheus - Dier, Erhard Amadeus, 1893-1969 (artist):::Creator:::::::::::: (2022)
Etching of expressionist image based on the myth of Prometheus, with a mask of Beethoven looking down upon a male figure receiving fire from the heavens. Inscribed "Beethoven Prometheus" and signed "EA Dier" by the artist, with date 1922.